Screening a bacterium and its effect on the biological degumming of ramie and kenaf - Lifeng Cheng (Scientia Agricola)
ABSTRACT: Biological degumming is an eco-friendly, efficient, high-quality and low-cost method that has become the leading bast fiber degumming technology. However, bacterial strains with short degumming cycles, high gum removal rates and small fiber damage are few. To screen high quality microbial resources with bast-fiber biological degumming function, soil samples were collected from a continuously cultivated banana plantation and then used to be enriched by ramie and kenaf materials in turn. A selective pectin-degrading medium was used to screen for excellent bacteria. A dominant bacterial strain was identified by phenotypic and genotypic characteristics, and its biological degumming effects on ramie and kenaf were verified by a comprehensive evaluation system. Results showed that seven bacterial strains secreting pectinase were obtained and the largest hydrolysis circle with a diameter ratio H/C of 2.4 was produced by the bacterial strain hn1-1, which was preliminarily identified as the Bacillus cereus by colony morphological characteristics and 16S rDNA sequence (GenBank accession number: KX013542) cluster analysis. The fiber production of ramie and kenaf degummed by B. cereus hn1-1 for 10 h were 72 % and 76 %, the residual gum rates were 4 % and 5 %, respectively. These values satisfied the textile industry requirement of < 6 % residual gum rate. Therefore, an effective biological degumming bacterium, B. cereus, was identified using a pectin-hydrolysis selective medium through a simple, economical, and time-saving method. Furthermore, the biological degumming technology by B. cereus for ramie and kenaf had a short cycle, ideal removal gum rate, and high-quality and productive fiber output.